2021
DOI: 10.3389/fpsyg.2021.634078
|View full text |Cite
|
Sign up to set email alerts
|

Culture Related Factors May Shape Coping During Pandemics

Abstract: This study aimed to examine how anxiety related to different styles of coping during the COVID-19 pandemic and how these relationships were moderated by the cultural orientations of individualism/collectivism and a person’s sense of meaning in life. A sample of 849 participants from Georgia completed an online survey during the final stage of lockdown. To measure the main variables, we used the State Anxiety Inventory, the Horizontal and Vertical Individualism and Collectivism Scale, the Meaning of Life Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 85 publications
(121 reference statements)
1
26
0
Order By: Relevance
“…Individuals with adequate resources to handle the stressors apply problem-focused coping (primary control). On the other side, individuals use emotion-focused coping (secondary control) when they encounter overwhelming challenges that are beyond their capacity to manage ( Shekriladze et al, 2021 ). During the COVID-19 lockdown, individualism and collectivism moderated the association between anxiety and passive–submissive coping styles ( Shekriladze et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with adequate resources to handle the stressors apply problem-focused coping (primary control). On the other side, individuals use emotion-focused coping (secondary control) when they encounter overwhelming challenges that are beyond their capacity to manage ( Shekriladze et al, 2021 ). During the COVID-19 lockdown, individualism and collectivism moderated the association between anxiety and passive–submissive coping styles ( Shekriladze et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, individuals use emotion-focused coping (secondary control) when they encounter overwhelming challenges that are beyond their capacity to manage ( Shekriladze et al, 2021 ). During the COVID-19 lockdown, individualism and collectivism moderated the association between anxiety and passive–submissive coping styles ( Shekriladze et al, 2021 ). Having self as a core unit of the society in individualistic orientations entails high priority of individual achievement and autonomy ( Shekriladze et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies using longitudinal methods could examine the stability of coping typologies over the course of the pandemic. We also did not include cultural or political measures that also may be relevant to appraisals of the pandemic and/or compliance [ 69 , 70 ]. Factors like willingness to comply with rules, conscientiousness, individualist versus collectivist values, and/or simple political affiliation might plausibly influence a person’s decision to comply or not.…”
Section: Discussionmentioning
confidence: 99%
“…However, countries with a lower prevalence or fatality rate of COVID-19 may have instituted more stringent control measures, which could lead to higher levels of anxiety [ 2 , 49 , 50 ]. An association between certain types of anxiety and adherence to protective measures such as hand hygiene and masking has been reported by some authors, suggesting that mild anxiety during a pandemic may be adaptive [ 27 , 51 ]. However, this explanation cannot be confirmed using the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are consistent with an earlier study that suggested that collectivistic cultures were associated with higher levels of alexithymia, which is a predictor of psychological distress [ 18 ]. A study of individuals from 26 countries showed that there was no significant association, either positive or negative, between cultural individualism/collectivism and stress related to the COVID-19 pandemic, while another study from a country with a moderate level of individualism showed that individualistic values were associated with active coping [ 27 , 59 ]. The relationship between culture and psychological responses to the pandemic may likely vary depending on the unit of analysis.…”
Section: Discussionmentioning
confidence: 99%